Active learning using deep Bayesian networks for surgical workflow analysis - Bodenstedt, Sebastian; Wagner, Martin; Müller, Beat P. (International journal of computer assisted radiology and surgery, 2019)
Purpose For many applications in the field of computer-assisted surgery, such as providing the position of a tumor, specifying the most probable tool required next by the surgeon or determining the...